2020
DOI: 10.3390/molecules25184265
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Daily Intake of Green Tea Catechins on Cognitive Function in Middle-Aged and Older Subjects: A Randomized, Placebo-Controlled Study

Abstract: Epidemiological studies in Japan, including the Nakajima study and the Tsurugaya study, have indicated that green tea consumption may improve cognitive impairment. Catechins, which are typical polyphenols contained in green tea, have been reported to have antioxidative, anti-inflammatory, and neuroprotective effects. However, their impact on human cognitive function remains unclear. Therefore, we performed a double-blind, randomized, controlled study to investigate the effect of 336.4 mg of decaffeinated green… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 38 publications
1
46
0
Order By: Relevance
“…Several studies have reported synergistic effects of caffeine and l -theanine on cognition and mood, 28 as well as on tasks related to attentional function. 18 Our results suggest that l -theanine by itself improves working memory. It remains possible that the improvement in attention, as described previously, 18 may have contributed to this effect.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Several studies have reported synergistic effects of caffeine and l -theanine on cognition and mood, 28 as well as on tasks related to attentional function. 18 Our results suggest that l -theanine by itself improves working memory. It remains possible that the improvement in attention, as described previously, 18 may have contributed to this effect.…”
Section: Discussionmentioning
confidence: 58%
“… 18 Our results suggest that l -theanine by itself improves working memory. It remains possible that the improvement in attention, as described previously, 18 may have contributed to this effect. In this study, after 12 weeks of regular ingestion, theanine had no effect on the processes related to attentional function as previously reported, even though our subjects had ages and MMSE scores similar to those of subjects in previous studies.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…It is thought to affect many psychological functions [ 2 ]. Thus far, we have shown that continuous matcha intake may slow the decline in cognitive function in older adults [ 8 ]. We assumed that this effect also included the effects of caffeine.…”
Section: Introductionmentioning
confidence: 99%
“…To block sunlight and increase the amino acid content, the tea leaves used for matcha are covered for approximately 20 days before they are plucked [ 9 ]. Matcha that is made using this method has a higher amino acid content than sencha and, in general, matcha has a lower catechin content than sencha [ 8 ]. After they are harvested, the dried leaves are ground into a fine powder.…”
Section: Introductionmentioning
confidence: 99%